(untitled) (Global Journal of Human-Social Science, 2017)
Major newsstands in Nigeria began over ten years ago to witness daily gathering of readers who spent hours to browse buy rent or discussnewspaper contents But there is hardly anyempirical research to explain this phenomenon beyond suggestions that the readers are football fans This study therefore set out to explore the characteristics and correlates of this novel reading behaviour using interviews obtrusive observation and questionnaire to collect datain Lagos Nigeria Findings indicate that newsstand reading sessions were characterised by information sharing prolonged by newspaper rental services dominated by male youths and advanced by the seasonality of football and politics Statistical analysis indicates that it is associated not only with the quest for football news as the literature suggested but also with the quest for political news The vendor-initiative of renting newspapers out implies that publishers may be losing sales through the rentals and explains why several newspaper publishers suddenly cancelled longstanding sale-or-return agreements